2021
DOI: 10.21203/rs.3.rs-699508/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Work-related Stressors and Mental Health Among LGBTQ Workers: Results From a Cross-sectional Survey

Abstract: Background: Lesbian, gay, bisexual, transgender, and queer (LGBTQ) individuals experience high rates of adverse mental health outcomes due to the stressors they experience in families, communities, and society more broadly. Work and workplaces also have the potential to influence these outcomes given the substantial amount of time spent at work, and the ability of work to further influence social and economic wellbeing in this already vulnerable population. This study aims to identify how sociodemographic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…All models were negative and significant. These results corroborate previous studies and others conducted during the COVID-19 pandemic that found a negative relationship between psychological distress and the occupational well-being of LGBTQIA+ people [28,29,[79][80][81]. Burnout seems to have the greatest impact on occupational well-being, followed by depression and anxiety, consecutively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All models were negative and significant. These results corroborate previous studies and others conducted during the COVID-19 pandemic that found a negative relationship between psychological distress and the occupational well-being of LGBTQIA+ people [28,29,[79][80][81]. Burnout seems to have the greatest impact on occupational well-being, followed by depression and anxiety, consecutively.…”
Section: Discussionsupporting
confidence: 91%
“…Studies carried out in Portugal and Brazil point to higher levels of psychological suffering, depression, anxiety, stress, and fears of losing wages or positions among LGBTQIA+ workers during this period [25][26][27], in addition to a worsening in work-related quality of life and occupational well-being [28]. In a qualitative study with 65 Brazilian and Portuguese LGBTQIA+ people, mental health problems were mentioned 78 times by the participants, and more than a quarter of the sample reported problems at work related to the pandemic context and their LGBTQIA+ identity [29].…”
Section: Introductionmentioning
confidence: 99%
“…Data for this study were collected as part of a community-engaged mixed methods study on the work, health and community experiences of LGBT workers in Windsor and Sudbury, Ontario ( Mills et al, 2020 ). Windsor and Sudbury are two mid-sized Canadian cities—with populations of 329,144 and 164,689, respectively ( Statistics Canada, 2017a , 2017b )—that are characterized by their industrial histories.…”
Section: Methodsmentioning
confidence: 99%
“…The study began with a community e-survey, administered between 6 July and 2 December 2018, that garnered 673 responses. Customer abuse and aggression emerged as a widespread issue facing LGBT workers: half of the 204 workers in the low-wage service sector reported experiencing abuse and/or aggression from customers, and workers who were transgender and/or racialized as people of colour reported customer abuse and aggression at significantly higher rates than those who were cisgender and/or racialized as white ( Mills et al, 2020 ). As a result, the authors sought to explore customer abuse and aggression in the qualitative phase of the study.…”
Section: Methodsmentioning
confidence: 99%
“…They are also more likely to rate their work environment as unfavorable for LGBTQ employees or to be unsure about it. Because they are more prone to turn to drugs and alcohol to cope with their jobs, LGBTQ employees who report having poor mental health are also more likely to lack adequate coping mechanisms (Mills et al, 2021). All of these were confirmed by a study conducted by Jayawardana and Priyashantha (2019) in Sri Lanka, who noted that the more diverse an organization's workforce is in terms of age, gender, educational level, job experience, and attitude, the better its employees' performance.…”
Section: Introductionmentioning
confidence: 99%